Technology Entertainment Design (TED) Talks to Stimulate Extensive Eistening Skills - Rahmawati, Taufikah Anisa; Thoyyibah, Luthfiyatun; Irianti, Leni (Universitas Galuh, 2025)
Listening in a foreign language can be challenging for learners. In the present era of education, technology plays a crucial role in facilitating learning through various tools. Mobile apps that utilize TED Talks for language learning can offer an innovative and effective approach to improving language skills. This research aims to investigate how students learn extensive listening through TED Talks and to determine the benefits of using TED Talks in extensive listening classes. This research is a case study under the approach of qualitative research and using case study. Participants in this research consisted of fourteen students majoring in English education at one of the higher education institutions in Ciamis, who were selected using a purposive sampling technique. The data collection method used in this current study included questionnaires, interviews, as complementary methods. To confirm the analysis of reliability, the researcher used a source of triangulation data by collecting, sorting, interpreting and concluding data. The results of research on the use of TED Talks to stimulate listening skills extensively showed that 50% of the students chose